Parent Factors are Associated with Pain and Activity Limitations in Youth with Acute Musculoskeletal Pain: A Cohort Study - Clementi, Michelle A. (Clin J Pain, 2019)
OBJECTIVES: Biopsychosocial models emphasize the influence of parent/family factors on pediatric chronic pain. Little is known about how parent factors differ across the acute to chronic pain continuum, or contribute to youths’ pain experience in the acute pain period. The purpose of the study was to describe parent factors in youth with acute musculoskeletal pain (n=84) compared to youth with chronic pain (n=60) and youth without pain (n=61). Further, within the acute pain sample, we tested parent factors as predictors of child pain characteristics, as well as the moderating role of child sex on associations. METHODS: Participants were 205 youth (ages 10–17) and one biological parent. Children reported on their own pain and activity limitations. Parents reported on their own chronic pain, somatization, and protective pain responses. RESULTS: Parents of youth with acute pain had higher prevalence of chronic pain and greater somatization than parents of youth without pain. Parents of youth with acute and chronic pain did not differ. Linear regressions within the acute pain sample revealed presence of parent chronic pain and protective behavior were associated with child pain. Moreover, parent somatization was associated with child activity limitations. Within the acute pain sample, associations between parent protectiveness and child pain were moderated by child sex, with relationships stronger for female children. DISCUSSION: Findings highlight the importance of parent factors on pain experiences of youth with acute musculoskeletal pain. Future longitudinal research can elucidate temporal associations that underlie how parent factors may impact transition from acute to chronic pain.